Sufism and Peace: The Profile and Role of Shaykh Husamuddin in the Deradicalisation Program - Suratno Suratno (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2022)
This article examines the contribution of Sufism to peace by studying the role of Shaykh Husamuddin Martin Mayer in the deradicalisation program in Germany. Shaykh Husam has a unique background as a convert (Muallaf), Sufi figure, anthropologist and peace activist. This study used a qualitative method in which the data were obtained through documentation studies and interviews. Data were analysed using the theory of the Sufism Peace Paradigm and the eight Stages of Psychosocial Development theory. This study revealed that Sufism correlates and could contribute positively to creating peace. This is evident in the profile of Shaykh Husam, a convert (muallaf) who then became a murshid of the Naqshbandi-Haqqani Order (NHO) and is active in the deradicalisation program in Germany. In his opinion, Sufism can function as a coping mechanism that is effective for today's social, political and religious challenges, including deradicalisation & peace programs, such as peace-making, peace-building, and peace-keeping.Contribution: This study contributes to revealing the role of sufism in creating peace and a deradicalisation program initiated by Shaykh Husam in Germany.